An update of the consensus statement on insulin resistance in children 2010 - Tagi, Veronica Maria; Samvelyan, Sona; Chiarelli, Francesco (Frontiers in Endocrinology, 2022)
In our modern society, where highly palatable and calorie rich foods are readily available, and sedentary lifestyle is common among children and adolescents, we face the pandemic of obesity, nonalcoholic fatty liver disease, hypertension, atherosclerosis, and T2D. Insulin Resistance (IR) is known to be the main underlying mechanism of all these associated health consequences; therefore, the early detection of IR is fundamental for preventing them. A Consensus Statement, internationally supported by all the major scientific societies in Paediatric Endocrinology, was published in 2010, providing all the most recent reliable evidence to identify the definition of IR in Children, its measurement, its risk factors, and the effective strategies to prevent and treat it. However, the 2010 Consensus concluded that further research was necessary to assess some of the discussed points, in particular the best way to measure insulin sensitivity, standardization of insulin measurements, identification of strong surrogate biomarkers of IR and the effective role of lifestyle intervention and medications in the prevention and treatment of IR. The aim of this review is to update each point of the consensus with the most recent available studies, with the goal of giving a picture of the current state of the scientific literature regarding IR in Children, with a particular regard for issues which are not yet fully clarified.